Strategic excellence in team sports tactics for victory - Adenan, Nur Dalila; Ngah, Nazlin Emiza; Abdullah, Nasiha; Abdul Talib, Nurafida; Mohamad Azmin, Nur Azwani (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2023)
Tactics in sports encompass the precise plans and methods employed by teams or individuals to effectively accomplish their objectives within the context of a game or competition. Tactical judgments are frequently rendered dynamically and are subject to modification based on the prevailing circumstances. Team sports allow for the study of a complex set of intra-group dynamics and the limitations that may be encountered in addressing these concerns (Fornari et al., 2023).